Emphasising the role of Environmental Law in pollution control toward public health protections - Mustafa, Maizatun; Fauzi, Husna (International Islamic University Malaysia, 2022)
The Coronavirus pandemic (COVID-19) which has globally impacted the social ecosystem is a combination of public health and environmental crises. Amidst the challenges faced in dealing with the consequences of the crises, the pandemic has unintendedly revealed the significance of the current environmental law system to protect human health from pollution. The pandemic has also heightened the realisation that environmental threats are driven by human activities. Consequently, COVID-19 has underscored the need of securing safe and clean surroundings and has emphasised the importance of having measures to protect human health. For Malaysia, strategies aiming at environmental protection could be found within the provisions of the Environmental Quality Act 1974 (EQA). Using the library-based research methodology on primary and secondary sources of law, this paper seeks to examine the scope of the EQA on public health protection and pollution control. Against the backdrop of sustainability, the research concludes that the interlinkages of environmental conservation and public health protection mean that the EQA is the most relevant law to attain these two interrelated objectives. It is submitted that COVID-19 has re-emphasised the importance of environmental law within the realm of health protection, which is in turn essential for the sustainable development agenda.